Construction, characterization, and bioavailability evaluation of honokiol-loaded porous starch by melting method without any solvent - Weiwei Wu; Haiyang Xu (Taylor & Francis Group, 2021)
In the present study, the porous starch (PS) was used as an efficient carrier of honokiol (HK), and the HK-loaded PS (HPS) delivery system was prepared by melting method without using organic solvents. Its physical-chemical properties, solubility and oral bioavailability were also investigated. The obtained results proved that the HK in the HPS was mostly amorphous when it was loaded into the PSs with 87.54 ± 1.52% of encapsulation efficiency (EE) and 12.51 ± 0.22% of drug loading (DL) capacity. The water-solubility of the HPS was increased to 115.27 ± 2.92 μg/mL (pH = 1.2, artificial gastric juice (AGJ)), 161.58 ± 3.42 (pH = 6.8, artificial intestinal juice (AIJ)) and 148.5 ± 1.89 μg/mL (pH = 5.5, simulated tumor microenvironment), being 6.07, 4.38 and 4.87-folds higher than free HK. In vitro dissolution tests showed the HK was significantly higher from HPS than from free HK. Furthermore, compared with free HK, the release rate and the bioavailability was also substantially improved for HK from the HPS. Meanwhile, the HPS generated a higher inhibition to HepG2 cells than free HK.